Kernel weight dependence upon plant growth at different grain-filling stages in maize and sorghum - Gambin, Brenda Laura (2008)
In the present study we tested how assimilate availability per kernel at different grain-filling stages may affect maize (Zea mays L.) and sorghum (Sorghum bicolor L. Moench) individual kernel weight (KW). These two species have shown a contrasting KW response to increased assimilate availability at similar seed developmental stages. Plant growth rate (PGR) per kernel was used to estimate the assimilate availability per kernel at two stages: around the early grain-filling period when kernel number per plant is also being established, and around the effective grain-filling period. We tested 3 commercial genotypes from each species, and modified the PGR by thinning or shading the stand at different developmental stages. In both species, each genotype showed a particular relationship between PGR around flowering and kernel number, which gave a range of responses in the PGR per kernel set around flowering. Final KW always increased whenever PGR per kernel around flowering was enhanced. Only sorghum showed a consistent KW increase when PGR per kernel during the effective grain-filling period was enhanced. Results confirmed that increasing assimilate availability per kernel will affect maize kernel size only if the potential set early in development is altered. Most important, we showed that linking specific KW sensibility across species at different seed developmental stages using a simple estimate of assimilate availability per seed (i.e. PGR per kernel) at each grain-filling stage helped explain most of the explored genotypic and environmental variability in final kernel size.